Susceptibility of eggs and adult fecundity of the lesser grain borer, Rhyzopertha dominica, exposed to methoprene - Y. Chanbang (2018)
A series of tests were conducted to determine the susceptibility of eggs and neonates of the lesser grain borer Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae = Bostrychidae), exposed to the insect growth regulator, methoprene, on filter paper and on rough rice. In the first test, the hatch rate of eggs exposed on filter paper treated with methoprene at the label rate of 0.003 mg [AI] /cm2 when used as a surface treatment in structures was 52.0 ± 7.3% compared to 93.0 ± 3.3% on untreated controls. In the second test, eggs were exposed to a dose-response series of 0.00003 to 0.03 mg[AI]/cm2. Egg hatch was directly proportional to concentration and ranged from 85.0 ± 2.0% on untreated controls to 26.7 ± 8.3% at the highest concentration tested. In the third test, 1 ppm of methoprene was sprayed on long grain rough rice (paddy) (Cocodrie variety), and then individual kernels were cracked and an egg of R. dominica was placed directly on the kernel. On untreated rice kernels, 67.5 ± 11.6% of the eggs hatched and were able to bore inside, and all of these larvae emerged as adults. In contrast, 40.0 ± 5.3% of the eggs placed on treated cracked kernels were able to develop to where the larvae were visible through X-ray detection, but none emerged as adults. In the final test, newly-emerged adults were exposed on rough rice treated with 1 ppm methoprene. The number of eggs from adults on untreated rice was 52.1 ± 4.3 eggs per female, and on treated rice the average egg production was 12.5 ± 1.1 eggs per female. Methoprene applied on a surface or on rough rice affected development of egg hatch also reduced fecundity of parent adults exposed on the treated rough rice.